Teaching organization and methodology in Kutaisi State Nobelman High School- Gymnasium – “Pedagogical Advice” - Basiladze, Imeri; Akhvlediani, Maia; Moralishvili, Sophio (International Scientific Conference “EDUCATION, RESEARCH, PRACTICE” Proceedings, 2024)
In 1880, The Kutaisi nobleman-land-bank Georgian State Nobelman High School- Gymnasium was founded on the initiative and financial assistance of the bank. To implement the Georgian educational process, it was necessary to create national educational programs, textbooks, and scientific terminology. The fulfillment of the national mission required proper organization and management. The teaching and educational processes in the school-gymnasium were led by the advisory "Pedagogical Advice ", which consisted of school teachers and the care committee. The gymnasium inspector led the said deliberative. The secretary was chosen by him to organize the "Pedagogical Advice" protocols. The deliberative included the best representatives of the teaching collective of the school gymnasium who made a special contribution to the development of Georgian scientific terminology, Georgian textbooks, and Georgian pedagogical thinking. Studying the archival materials reveals that the "Pedagogical Advice" as a deliberative had a methodological function as well. Based on the analysis of existing archival documents, it can be safely said that "Pedagogical Advice" successfully managed the first Georgian educational institution in western Georgia despite the background of the problems characteristic of that era. "Pedagogical Advice " was administrating the most difficult task of education and teaching in the Georgian language based on the modern principles of pedagogy. From the first days of its establishment, it raised the next generation with a national spirit. Their approach to all problematic issues was creative and based on the interests of students, teachers, school and country.